The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-020-78070-2
|View full text |Cite
|
Sign up to set email alerts
|

High yield synthesis of graphene quantum dots from biomass waste as a highly selective probe for Fe3+ sensing

Abstract: Graphene quantum dots (GQDs), a novel type of zero-dimensional fluorescent materials, have gained considerable attention owing to their unique optical properties, size and quantum confinement. However, their high cost and low yield remain open challenges for practical applications. In this work, a low cost, green and renewable biomass resource is utilised for the high yield synthesis of GQDs via microwave treatment. The synthesis approach involves oxidative cutting of short range ordered carbon derived from py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(85 citation statements)
references
References 98 publications
6
78
1
Order By: Relevance
“…In this respect, the introduction of spatial statistics tools can provide a substantial support to this type of investigation by providing metrics (such as the here used uniformity index) to further expand the description of the complex structure of this tissue environment. As recently documented in a methodological study [ 27 ] based on CD68-positive macrophages within human head and neck tumors, combinations of spatial statistics-derived parameters can lead to better predictions of macrophage infiltration than any classical morphometric method. This type of approach, therefore, may provide a more accurate description of the functional status of the tumor, potentially leading to a better view on patient prognosis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, the introduction of spatial statistics tools can provide a substantial support to this type of investigation by providing metrics (such as the here used uniformity index) to further expand the description of the complex structure of this tissue environment. As recently documented in a methodological study [ 27 ] based on CD68-positive macrophages within human head and neck tumors, combinations of spatial statistics-derived parameters can lead to better predictions of macrophage infiltration than any classical morphometric method. This type of approach, therefore, may provide a more accurate description of the functional status of the tumor, potentially leading to a better view on patient prognosis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…As recently documented in a methodological study [ 27 ] based on CD68-positive macrophages within human head and neck tumors, combinations of spatial statistics-derived parameters can lead to better predictions of macrophage infiltration than any classical morphometric method. This type of approach, therefore, may provide a more accurate description of the functional status of the tumor, potentially leading to a better view on patient prognosis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The obtained GQDs showed high biocompatibility and effectiveness for the detection of intracellular temperature. More recently, Abbas et al [ 66 ] synthesized GQDs from tea waste by the microwave assisted oxidative process followed by a hydrothermal treatment in designing selective fluorescent sensors for the detection of the Fe 3+ metal ion. The tea scraps were previously washed and dried for 12 h and, subsequently ground.…”
Section: Gqds From Eco-friendly Raw Materials By Green Approachesmentioning
confidence: 99%
“…The use of these methods (thermal pyrolysis and hydro/solvothermal) is pretty challenging since they exhibit a change in reactor temperature, thereby providing uncontrolled size and structure 89 . To overcome these issues, microwave assisted bottom-up synthesis gained increased interest in view of its several benefits such as high yield, energy saving, reproducibility, low impurity and short reaction time 95,[104][105][106][107] . From this perspective, Tang et al reported a microwave-assisted synthetic method, wherein glucose solution was irradiated with microwave in the NH3 environment (Figure 2D).…”
Section: Bottom-up Approachesmentioning
confidence: 99%